Natural-source bioceramics and controlled drug release applications - AYAZ SEYHAN, SERAP (Nova Science Publishers, 2023)
his volume contains eight chapters that detail advances in nanotechnology. Chapter One provides a thorough understanding of the effects of optical cavities and plasmonics and their applications. Chapter Two focuses on various nanocarrier approaches that evolved in recent times, the challenges, and future perspectives in ocular drug delivery systems. Chapter Three provides a comprehensive overview of the synthesis, properties, and particularly energy applications of elemental boron (EB) and boron-based hybrid nanomaterials using electrosynthesis techniques. Chapter Four summarizes the improvements in clinical diagnosis, detection, and therapeutic applications of nanoparticles against HBV and HCV viral infections. Chapter Five aims to determine the influence of the addition of metallic iron nanoparticles on the removal of lindane and the generation of bioelectricity in a soil slurry bioelectrochemical reactor (SSBER). Chapter Six provides information on various literature studies reported on drug release studies of naturally-synthesized hydroxyapatite (HA) composites. Chapter Seven sheds light on updated patents and advancements in nanosuspension technology, encompassing diverse drug molecules, instrumental techniques, and characterization parameters. Lastly, Chapter Eight investigates a piezoelectric actuator with coded control for use in nano research.